Simulação do movimento miscível de sais e água em colunas de solo por aplicação de efluente de esgoto doméstico tratado - Suszek, Floriano Luiz (2018)
The increasing production of agro-industrial and urban wastes has engendered huge impacts on the environment. Such wastes, when treated, can be reused in agriculture as an input supplementation. So, wastewater reuse is an alternative to avoid environmental impacts and reduce the consumption of potable water, although, there is some risk of soil salinization when it is applied in the chosen area. Thus, this trial aimed at simulating scenarios for the movement of water and solutes when some domestic sewage wastewater is applied in columns of two kinds of tropical soils, in order to verify the efficiency of HYDRUS-1D program. Therefore, data collection methodologies were carried out for the simulator program application and entry into the simulator as well as the data of comparison with the simulated ones. A simulation efficiency for water movement into a soil becomes satisfactory for long leaching processes, since it reduces the error over time, and it is better represented by the Chromic Luvisol. The miscible movement simulation of solutes into soils was better observed than in Chromic Luvisol with saline solution for ion sodium and in the Regolithic Entisol with domestic wastewater for ions such as potassium, calcium and magnesium. Magnesium ion has shown at least a satisfactory index for all analyzed scenarios. Potassium and calcium ions were not efficient simulated in Chromic Luvisol. Finally, the program weakness in simulating some scenarios shows that it is required the increase of other parameters or methodologies, in order to make the results more efficient.